Efektifitas Pemberian Tablet Fe dan Buah Pisang Ambon Dalam Meningkatkan Kadar Hemoglobin - Erni Muslikah; Sulastri Sulastri (Jurnal Berita Ilmu Keperawatan, 2018)
: An effort to overcome anemia can be done by administering iron tablets containing 30-60 mg of iron and 400 mg of folic acid. Ambon bananas contain iron, vitamin B6, and vitamin C which can provide antioxidant benefits in enhancing the immune system and help maximize iron absorption. This study aims to determine the effectiveness of Fe tablets and ambon bananas with Fe tablets in increasing hemoglobin levels. This type of research is a quasi quasi-pretest-posttest two group design experiment. The number of samples is 30 respondents. The distribution of the sample is 15 respondents given Fe tablets and ambon bananas and 15 respondents only given Fe tablets. The results of this study Paired Sample T-Test, the significance value or p-value of Fe tablets and ambon bananas amounted to 0,000, with an average Hb pre-test 10,540 g / dl and post-test 13,840 g / dl or an increase of 3.3 g / dl and the significance value or p-value of Fe tablets of 0,000, with an average Hb pre-test 11,060 g / dl and post-test 12,267 g / dl or an increase of 1.2 g / dl. The conclusion of this study showed that there was a significant difference in the increase in hemoglobin levels between the Fe tablet and ambon banana groups and the Fe tablet group.